Consumer Purchase Decisions of Halal-Certified Food Product: A Systematic Literature Review - Agnesia, Ovilly; Faridah, Anni (Academia Open, 2026)
General Background: Consumer decision-making in the food sector increasingly reflects ethical, cultural, and religious considerations beyond functional attributes. Specific Background: Halal-certified food products represent a growing global market segment, where certification signals compliance with Islamic principles, food safety, and product quality. Knowledge Gap: Existing studies remain fragmented, often focusing on isolated determinants and relying heavily on purchase intention rather than actual buying behavior, with limited attention to contextual and technological influences. Aims: This study aims to systematically review empirical research on consumer purchase decisions of halal-certified food products to identify key determinants, conceptual approaches, and research gaps. Results: The findings reveal that purchase decisions are shaped by interconnected factors including halal certification, trust and certification credibility, religiosity, product attributes such as taste and quality, health considerations, and socio-economic influences, with evidence indicating that product attributes can outweigh halal status in certain contexts. Consumer perceptions are multidimensional, encompassing religious compliance, trust, ethical values, and perceived quality, and are primarily measured using survey-based methods, with emerging approaches such as discrete choice experiments and willingness-to-pay analysis providing deeper insights. Novelty: This review synthesizes diverse empirical evidence into an integrated framework that categorizes determinants and highlights the multidimensional nature of consumer evaluations. Implications: The study underscores the need for behavior-focused, context-sensitive, and integrative research approaches to better capture real-world consumer decisions in halal food markets. Highlights• Identifies seven interconnected categories shaping purchasing choices in halal food markets• Reveals sensory attributes and perceived quality may surpass certification cues in specific contexts• Highlights methodological limitations and need for behavior-oriented research approaches KeywordsHalal Certified Food; Consumer Behavior; Purchase Decision; Halal Certification; Systematic Literature Review